(untitled) (Research, Society and Development, 2021)
The present study aimed to verify the absence of patients with special needs in three Regional Dental Specialties Centers (CEO-R), located in the Cariri region. The data were obtained through the Integrated Health Management System in Ceará. In order to verify the association between distance and number of absences, Pearson’s correlation analysis was performed and to describe the geographic pattern of the occurrence of absences, thematic maps were built based on the distributions of the absentee rates. When correlating the variables, there is a statistically significant correlation for distance and percentage of absences (p = 0.003) distance and scheduled patients (p = 0.025), distance and confirmed patients (p = 0.018) and distance and completed treatments (p = 0.016). It can be concluded that patients ’absences do not occur seasonally and that the distance to the CEO can be a predictor that presented a positive correlation and strong association with patients’ absenteeism.